New results on dynamic instability of Antarctic Peninsula glaciers detected by TerraSAR-X ice motion analysis - Rott, Helmut; Eineder, Michael; Nagler, Thomas; Floricioiu, Dana (VDE Conference Services, 2008)
Larsen-A ice shelf in 1995 and Larsen-B in 2002. Retreat and acceleration was observed for the glaciers above the previous Larsen-A ice shelf between 1995 and 1999 by means of 24 hour repeat pass ERS-1/ERS-2 InSAR data. Because the signal over glaciers decorrelates rapidly, no InSAR analysis was possible later on with ASAR. New opportunities for ice dynamic studies were opened up by TerraSAR-X. We applied image correlation techniques with 11-day repeat pass data, acquired in strip-map mode with 3m x 3m resolution to map ice motion. Up to eight-fold acceleration of the terminal parts of glaciers was observed since the ice shelf collapse, resulting in significant increase of export of grounded ice which contributes to sea level rise. These investigations demonstrate that TerraSAR-X offers unique opportunities for studies of flow dynamics of glaciers and ice streams. The high spatial resolution and short repeat observation capabilities enable detailed observations of complex flow fields and their temporal variations.